How do energy policies affect industrial green development in China: Renewable energy, energy conservation, or industrial upgrading? - Jingjing Zeng; Wensi Tong; Tian Tang (Chinese Journal of Population, Resources and Environment, 2020)
The industrial sector has accounted for approximately 70% of China's total energy consumption over the past 30 years. Achieving green development is thus an important strategic goal of the Chinese industrial sector. The Chinese government has adopted various energy policies to facilitate industrial green development. Due to their different goals, these policies may have different impacts on the promotion of green development in the industrial sector. Using panel data on 31 provinces from 2007 to 2014, we examine the effects of three types of energy policies—renewable energy, energy conservation, and industrial upgrading—on industrial green development in China, measured using reduced energy intensity. Our empirical findings suggest that all three types facilitate industrial green development. However, effectiveness varies by policy type and region. Renewable energy and energy conservation policies have stronger impacts than policies aiming at upgrading traditional fossil fuel industries. Moreover, it takes longer for the effectiveness of industrial upgrading policies to be manifested, compared with the other two types. We discuss the implications of these empirical findings for future policymaking in promoting industrial green development.